Molecular Biomarkers in Traumatic Brain Injury: Diagnostic, Prognostic, and Therapeutic Perspective - Setiasari, Febi Jian; Putri, Shaffani Mahasuary; Puspasari, Baiq Sagitta; Ilham, Muhammad Fadani (Jurnal Biologi Tropis, 2025)
Traumatic Brain Injury (TBI) remains a major global health problem due to its high morbidity and mortality rates. TBI can lead to cognitive and emotional impairments, and even increase the risk of neurodegenerative diseases such as Alzheimer's and Parkinson's. This review was compiled by searching literature discussing the role of molecular biomarkers in TBI, both from diagnostic and prognostic perspectives, as well as their therapeutic potential. The article search was conducted via PubMed, ScienceDirect, and Google Scholar using relevant keywords. The findings showed that with the increasing number of TBI cases, the limitations of CT scans and the Glasgow Coma Scale (GCS) in assessing subtle brain damage have spurred interest in molecular biomarkers. Biomarkers such as GFAP, S100B, tau protein, UCH-L1, and NF-L have been shown to detect biological changes not visible on routine imaging. GFAP emerges as the most promising candidate due to its high sensitivity and specificity in assessing injury severity. Thus, molecular biomarkers have the potential to improve diagnostic accuracy, predict prognosis, and support more effective rehabilitation strategies. The conclusion is that TBI is a global health problem with serious long-term impacts. Molecular biomarkers offer a great opportunity to complement conventional diagnostic methods. Although challenges remain in validation, standardization, and clinical application, further research can pave the way for the use of biomarkers as diagnostic and prognostic tools, as well as a basis for more personalized therapy in TBI patients.